Maritime merchandise trade in Southeast Asia : opportunities and challenges - Lee, YingHui (2021)
While maritime merchandise trade brings about significant opportunities for growth in Southeast Asia, the dependency on maritime merchandise trade also brings about risks and challenges. This paper begins with a brief examination of the maritime merchandise trade situation globally and in Southeast Asia, followed by a discussion of initiatives undertaken to promote maritime merchandise trade in the region. In doing so, the paper makes three key propositions. First, concentration of trade among a few trading partners and the large maritime infrastructure and logistics gap among the Association of Southeast Asian Nations (ASEAN) member states are the two main challenges facing Southeast Asia. Second, case studies of Indonesia and Singapore show that diverse interests and capabilities among ASEAN member states underscores the need for different national strategies for promoting maritime merchandise trade. Third, both traditional and non-traditional maritime security threats constitute significant risk to maritime merchandise trade in Southeast Asia.